A comparative study of some lithium and hydrogen‐bonded complexes: Ab initio and QTAIM studies. Issue 6 (5th November 2013) - Zhang, Xueying; Li, Xiaoyan; Zeng, Yanli; Meng, Lingpeng; Zheng, Shijun
<x xml:space="preserve">Abstract</x> The nature of the interactions of cyanide with lithium and hydrogen halides was investigated using ab initio calculations and topological analysis of electron density. The computed properties of the lithium‐bonded complexes RCN···LiX (R = H, F, Cl, Br, CCH, CHCH2, CH3, C2H5; X = Cl, Br) were compared with those of corresponding hydrogen‐bonded complexes RCN···HX. The results show that both types of intermolecular interactions are "closed‐shell" noncovalent interactions. The effect of substitution on the interaction energy and electron density at the bond critical points of the lithium and hydrogen bonding interactions is similar. In comparison, the interaction energies of lithium‐bonded complexes are more negative than those of hydrogen‐bonded counterparts. The electrostatic interaction plays a more important role in the lithium bond than in the hydrogen bond. On complex formation, the net charge and energy of the Li atom decrease and the atomic volume increases, while the net charge and energy of the H atom increase and the atomic volume decreases. © 2013 Wiley Periodicals, Inc.